Methods of technique creative process at the lessons of decorative and applied arts for the speciality “Engineering” - Крижановський, Микола Миколайович; Фурман, Олександр Іванович (Pedagogy of Higher and Secondary Education, 2015)
Kryzhanovskyy M. М, Furman A. I. Methods of technique creative process at the lessons of decorative and applied arts for the speciality “Engineering”. The article deals with problem of methods for creating ornamental image at the lessons of decorative and applied arts for the speciality engineering and drawing. It is shown that creation of decorative and applied arts works by the future teachers of engineering depends on technically appropriate creative process.